Interest Rate Risk of Bonds in the Condition of a Changing Key Rate - N. V. Popova (Финансы: теория и практика, 2022)
The article is devoted to the analysis of the behavior of the interest rate risk of bonds in the conditions of a changing key interest rate. As known, the key rate is an instrument of monetary regulation of the Central Bank of the Russian Federation. During periods of instability, the key rate may change, which leads to changes in yields in the bond market. The latter, in turn, means that bonds on the Russian market are exposed to interest rate risk. When investing in federal loan bonds (OFZ), interest rate risk becomes the main type of risk, since there is no credit risk in such bonds. The aim of the paper is to obtain proof of the dependence of the interest rate risk of bonds on the term to maturity. The author applies methods of differential calculus to obtain the proof. The novelty of the research is that there is no similar proof in the literature. The instability of interest rates in the market persists at the present time, which allows us to speak about the relevance of this work. Results: it is established that with fixed values of the coupon rate, initial yield and the amount of interest rate change, the interest risk of bonds increases with an increase in the term to maturity. For longterm bonds sold at a discount, there is a term of a maximum interest rate risk. The formula for the approximate value of the term of maximum is obtained. Proven statements are confirmed by calculations, are consistent with previously performed studies, and are in line with market observations. The author comes to the conclusion that the proof obtained in the article of the dependence of the interest rate risk of bonds on the term to maturity can be used to analyze the behavior of the interest rate risk of bonds in the conditions of a changing key interest rate. The practical significance: the results of the research can be useful to the issuer and investor, as well as in theory when studying the investment properties of bonds.